Vectorial transport of proteins into and across membranes - Tartakoff, Alan Michael (Methods in cell biology, 1991)
This is the third volume in this series covering protein translocation within and between cells. Volumes 31 and 32, Vesicular Transport, Parts A and B, treated techniques for eukaryotic cells available as of 1989. This volume, Vectorial Transport of Proteins into and across Membranes, brings together new methods and new topics as of 1991. Highlights include use of anti-idiotype antibodies, gene fusions, transcription, crosslinking, pulse-labeling, and reconstitution. Key Features * Describes contemporary approaches for studying * Protein transport * Protein topology * Organelle biogenesis * Covers methods from pre-eminent laboratories including * In vitro and in vivo investigations * Biochemical and immunological techniques * Prokaryote, chloroplast, mitochondria, peroxisome, and rough endoplasmic reticulum membranes.